2018
DOI: 10.1016/j.otsr.2018.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Ulnar variance according to gender and side during aging: An analysis of 600 wrists

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…Our study demonstrated that negative ulnar variance is lower in men than in women. This is consistent with the results by Nakamura et al (26), Jung et al (24), Elsaftawy (27), and Sayit et al (28). However, some other studies did not show any association between ulnar variance and sex (2,29,30).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study demonstrated that negative ulnar variance is lower in men than in women. This is consistent with the results by Nakamura et al (26), Jung et al (24), Elsaftawy (27), and Sayit et al (28). However, some other studies did not show any association between ulnar variance and sex (2,29,30).…”
Section: Discussionsupporting
confidence: 93%
“…Recently, excellent reliability (ICC value 0.94) was documented for computer-aided analysis using the CRP as a reference point for the measurement of ulnar variance (8) Our study demonstrated that negative ulnar variance is lower in men than in women. This is consistent with the results by Nakamura et al (26), Jung et al (24), Elsaftawy (27), and Sayit et al (28). However, some other studies did not show any association between ulnar variance and sex (2,29,30).…”
Section: Discussionsupporting
confidence: 92%
“…Nakamura et al stated that negative UV is higher in men (11). However, in some studies, no relationship was found between UV, age, and sex (2,8,35,36). In our study, we found that men were more common in the neutral variance group and women in the positive variance group ( P < 0.05).…”
Section: Discussionmentioning
confidence: 95%
“…There have been many studies on ulnar variance that describes the relative length of the radius with respect to the ulna (Fu et al., 2009; Jung et al., 2001; Sayit et al., 2018; Yeh et al., 2001; Yoshioka et al., 2007). It has been shown that ulnar variance changes in different forearm positions, elbow positions and with hand grip (Fu et al., 2009; Jung et al., 2001; Yeh et al., 2001).…”
Section: Methodsmentioning
confidence: 99%